The Effectiveness of Edmodo Educational Platform in Developing Achievement and Attitude towards Science Subject among Ninth-Grade Students in Jordan - Fatima Khaled Al-Nawaisah (Britain International for Academic Research (BIAR) Publisher, 2022)
The current study aimed to reveal the effectiveness of the educational platform Edmodo in developing achievement and developing the trend toward science among ninth-grade students in Jordan. The study was applied during the second semester of the academic year 2021-2022. The researcher used the experimental method, where she prepared an achievement test to measure the extent to which students attain the topics of a proposed unit in science at the levels of remembering, understanding, application, and higher levels (analysis and synthesis), and a measure of attitudes towards sciences was used. The study sample consisted of (40) female students from Al-Mazar Secondary School for Girls. The results of the research revealed that there were statistically significant differences at the significance level (a < 0.05) in the effectiveness of the Edmodo educational platform in developing science achievement among ninth-grade students in favor of the post application. In addition, there were statistically significant differences at the significance level (a < 0.05) in the effectiveness of the Edmodo educational platform in developing the attitude towards science among ninth-grade students in favor of the post application. In light of the findings of the study, the researcher recommends; Training teachers to use Edmodo e-learning platforms, benefiting from the experiences of developed countries in the field of interactive curricula programming.